Planning and Implementation Enterprise Resource Planning Module Distribution Management Using the Methods of Distribution Requirement Planning in MSMES UD Adhi Teknik - Nugroho, Mulyanto; Dwi Ellianto, Mario Sarisky; Nurcahyo, Yusuf Eko (International Review of Management and Marketing, 2019)
The integration of computerization in the company allows the groove and access to information in the company can quickly and accurately are reinforced on all fronts. The integration of computerized currently used large companies to compete and develop is enterprise resource planning (ERP). ERP is the integration of all the process of information data on the organization into a system of software and hardware to achieve integration. distribution requirement planning (DRP) is an operating system (production, procurement, atonia material, product distribution) occurs only as a response to the scheduling planning for every operation without taking into account the status of the real-time from the corresponding operation. MSMES of skewer making machine have the name of UD. Adhi teknik of standing since the year 2008 is moving in the field of making the machine as satay. MSMES is located in Terung Kulon, Sidoarjo, East Java. This company does not have a Distribution management system so that the process of distribution of these companies are still experiencing delays and good in the process of production and distribution process company products to customers who cause the swelling production cost, the cost of distribution and becomes dissatisfied by the customer. The method of calculation DRP produce cost savings compared to the method used by the company. Besides that the interval is also more than the previous one. With ERP information system technology also accelerate the flow of information between the department and also the sale and purchase of. Keywords: Information System, Enterprise Resource Planning Adempiere, Distribution Requirement Planning, MSMES UD Adhi Teknik JEL Classifications: P4, P42 DOI: https://doi.org/10.32479/irmm.8092